Unraveling the molecular mechanisms and the potential chemopreventive/therapeutic properties of natural compounds in melanoma. (December 2019) - Fontana, Fabrizio; Raimondi, Michela; Di Domizio, Alessandro; Moretti, Roberta M.; Montagnani Marelli, Marina; Limonta, Patrizia
Abstract: Melanoma is the most fatal form of skin cancer. Current therapeutic approaches include surgical resection, chemotherapy, targeted therapy and immunotherapy. However, these treatment strategies are associated with development of drug resistance and severe side effects. In recent years, natural compounds have also been extensively studied for their anti-melanoma effects, including tumor growth inhibition, apoptosis induction, angiogenesis and metastasis suppression and cancer stem cell elimination. Moreover, a considerable number of studies reported the synergistic activity of phytochemicals and standard anti-melanoma agents, as well as the enhanced effectiveness of their synthetic derivatives and novel formulations. However, clinical data confirming these promising effects in patients are still scanty. This review emphasizes the anti-tumor mechanisms and potential application of the most studied natural products for melanoma prevention and treatment.